upaya Upaya Meningkatkan Penjualan Keripik Tempe Singkong Bu Boinah Melalui Labeling Kemasan di Dukuh Mening Prajegan Sukorejo - Hanuf Fatkhul Janah; Khoirul Fathoni (Social Science Academic, 2025)
This study aims to identify efforts to increase sales of Bu Boinah's cassava tempeh chips through the application of packaging labeling in Dukuh Mening Prajegan Sukorejo. Effective packaging labeling can play an important role in attracting consumer attention and increasing product competitiveness in stalls or shops. considering that cassava tempeh chips are the people’s favorite food. This research method is the ABCD (Asset Based Community-Driven Development) approach, with the steps taken are inculturation, discovery, design, define, and reflection. The strategies used to increase sales of tempe chips business in Hamlet Mening, Prajegan Village, Sukorejo, Ponorogo Regency are: (1) Improving packaging to increase consumer attractiveness (2) Providing product labels on cassava tempe chip packaging 3) Expanding marketing networks by utilizing information and communication technology on line.. The result of this study is that efforts to increase sales through labeling labeling can increase product visibility, attract buyers, and strengthen the brand image of Bu Boynah's cassava tempeh chips. Strengthen the brand image of Bu Boinah's cassava tempeh chips. This research provides guidance for small businesses in designing and implementing effective labeling strategies to increase product attractiveness and effective labeling strategies to increase product appeal and sales.